EQUIPMENT AND ENVIRONMENT OF FITNESS FACILITIES: THE PERSPECTIVE OF FITNESS INDUSTRY EMPLOYEES. Issue 7 (11th March 2014) - Gray, S; Keyzer, P; Norton, K; Dietrich, J; Sekendiz, B; Coyle, I; Finch, C
Abstract : Background: Fitness facilities provide an avenue for people to engage in physical activity, however it is important that these facilities do all in their power to reduce the likelihood of injuries occurring. The attitudes and practices of those employed in the fitness industry with respect to risk management are important for implementation of injury prevention measures, as are risk management procedures currently in place. Objective: To identify views of the fitness industry employees about injury risks and hazards associated with equipment and training environments within fitness facilities and their risk management and hazard identification practices in relation to them. Design: A 6-week nationwide online survey. Setting: Australia-wide fitness industry. Participants: 1 178 adults across Australia who own, manage or work in the fitness industry. Main outcome measurements: Responses to 6-point Likert scale questions. Results: 79.1% of survey respondents held the safety of the fitness premises in high importance, and 80.2% stated that the location and condition of their facility (access, lighting, floor surfaces etc.) was very/extremely safe. The layout of equipment in the facility was very/extremely good in 61.9% of cases, and fitness equipment maintenance was reported to have been conducted frequently by 68.5% of the respondents. Fitness employees frequently observed hazardous conditions of the exercise areas with respect to objects lying around (43.8% of cases), equipment misuse (41.9% of cases), and facility users lifting weights that were considered too heavy (47.8% of cases). Conclusion: The findings suggest that facility users should be provided with further education regarding their physical activity programs and behaviours that could reduce injury risk, and that guidelines for using the facility should be made more obvious. The findings also indicate that fitness industry employees should be given risk management training, and that in facilities where hazards were observed and hazardous practices are engaged in, that risk analysis and management protocols need to be implemented.